Antibacterial Activity of Ethanolic Extract of Leaves and Bulb of Allium sativum Linn. against Shigella sonnei - Sacharina, Dewi; Anggraeni, Safitri Nur; Asmitha, Suci Miranda; Nobela, Deandra; Kusumowati, Ika Trisharyanti Dian (Proceeding ISETH (International Summit on Science, Technology, and Humanity), 2016)
Garlic (Allium sativum Linn.) is widely known by people as herb, besides having antibacterial property. Alisin is one of antibacterial active substance contained in garlic. The purpose of this study was to test the antibacterial activity of ethanol extracts of garlic leaves and bulbs against Shigella sonnei or dysentery bacteria. The determination of antibacterial activity was conducted by using disk diffusion and dilution methods. Antibacterial test results which had the best inhibitory activities against Shigella sonnei were shown by the extracts of 8% garlic bulbs and 4% garlic leaves with inhibition zone respectively 16mm and 19mm. The result showed the MIC of garlic bulbs extract was 0.5% and garlic leaves extract was 0.25%. The smallest concentration which could kill (MBC) Shigella sonnei was garlic bulbs extract 1% and garlic leaves extract 0.5%. This study showed that the ethanol extracts of garlic leaves and bulbs had antibacterial activity against Shigella sonnei.